Incidence of encephalopathy and comorbidity in infants with perinatal asphyxia: a comparative prospective cohort study - Cristina Vega-del-Val; Juan Arnaez; Juan Arnaez; Juan Arnaez; Carlos Ochoa-Sangrador; Carlos Ochoa-Sangrador; María Garrido-Barbero; Alfredo García-Alix; Alfredo García-Alix (Frontiers in Pediatrics, 2024)
BackgroundPrograms that aim to improve the detection hypoxic-ischemic encephalopathy (HIE) should establish which neonates suffering from perinatal asphyxia need to be monitored within the first 6 h of life.MethodAn observational prospective cohort study of infants with gestational age ≥35 weeks, and above 1,800g, were included according to their arterial cord pH value (ApH): ≤7.00 vs. 7.01–7.10. Data was collected including obstetrical history, as well as neonatal comorbidities, including the presence of HIE, that happened within 6 h of life. A standardized neurological exam was performed at discharge.ResultsThere were 9,537 births; 176 infants with ApH 7.01–7.10 and 117 infants with ApH ≤7.00. All 9 cases with moderate-to-severe HIE occurred among infants with ApH ≤7.00. The incidence of global and moderate-severe HIE was 3/1,000 and 1/1,000 births, respectively. Outcome at discharge (abnormal exam or death) showed an OR 12.03 (95% CI 1.53, 94.96) in infants with ApH ≤7.00 compared to ApH 7.01–7.10 cohort. Ventilation support was 5.1 times (95% CI 2.87, 9.03) more likely to be needed by those with cord ApH ≤7.00 compared to those with ApH 7.01–7.10, as well as hypoglycemia (37% vs. 25%; p = 0.026). In 55%, hypoglycemia occurred despite oral and/or intravenous glucose administration had been already initiated.ConclusionsCord pH 7.00 might be a safe pH cut-off point when developing protocols to monitor infants born with acidemia in order to identify infants with moderate or severe HIE early on. There is non-negligible comorbidity in the ApH ≤7.00 cohort, but also in the 7.01–7.10 cohort.